2022
DOI: 10.3390/cancers14041074
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Panel Sequencing of DNA Variants in cf-, ev- and tumorDNA for Pancreatic Ductal Adenocarcinoma Patients

Abstract: Pancreatic ductal adenocarcinomas (PDACs) are tumors with poor prognosis and limited treatment options. Personalized medicine aims at characterizing actionable DNA variants by next-generation sequencing, thereby improving treatment strategies and outcomes. Fine-needle tumor biopsies are currently the gold standard to acquire samples for DNA profiling. However, liquid biopsies have considerable advantages as they are minimally invasive and frequently obtainable and thus may help to monitor tumor evolution over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Similar studies have indicated the presence of larger DNA fragments within EVs (Mao et al, 2019;Nguyen et al, 2020;Ruhen et al, 2021). It has been reported that longer EV-DNA fragments may improve the detection of single nucleotide variations, copy number variations (San Lucas et al, 2016) and insertions/deletions during NGS sequencing performance and bioinformatic analysis (Waldenmaier et al, 2022). However, other studies reported the presence of shorter DNA fragments (152.4 bp, 160 bp) within EVs, with larger DNA fragments possibly resulting from contamination with apoptotic bodies (Sun et al, 2021;.…”
Section:  Ev-dna Fragment Size Profilementioning
confidence: 63%
See 1 more Smart Citation
“…Similar studies have indicated the presence of larger DNA fragments within EVs (Mao et al, 2019;Nguyen et al, 2020;Ruhen et al, 2021). It has been reported that longer EV-DNA fragments may improve the detection of single nucleotide variations, copy number variations (San Lucas et al, 2016) and insertions/deletions during NGS sequencing performance and bioinformatic analysis (Waldenmaier et al, 2022). However, other studies reported the presence of shorter DNA fragments (152.4 bp, 160 bp) within EVs, with larger DNA fragments possibly resulting from contamination with apoptotic bodies (Sun et al, 2021;.…”
Section:  Ev-dna Fragment Size Profilementioning
confidence: 63%
“…Similar studies have indicated the presence of larger DNA fragments within EVs (Mao et al., 2019 ; Nguyen et al., 2020 ; Ruhen et al., 2021 ). It has been reported that longer EV‐DNA fragments may improve the detection of single nucleotide variations, copy number variations (San Lucas et al., 2016 ) and insertions/deletions during NGS sequencing performance and bioinformatic analysis (Waldenmaier et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%